Roti john cha cha cha : roti john and beverage / Abdur Fattah Abd Kadir ...[et al.] - Abd Kadir, Abdur Fattah; Norhisham, Mohammad Farhan; Ayu Dian, Casuarina Nisha; Insol, Genveana Laura; Sazali, Puteri Aisyah Khairina (2022)
This company is run as a partnership, with five members each holding a key position in the organisation, such as General Manager, Administration Manager, Marketing Manager, Operations Manager, and Financial Manager. Roti John Cha Cha Cha provides a variety of Roti John such as Roti John ayam classic, Roti John daging classic, Cheezy Roti John, Pattaya Roti John and Mozzarella cheese Roti John and we also serve juice drinks. Roti John Cha Cha Cha is a firm based in Ulu Tiram, Johor Bahru. Its address is at 45, Jalan Gaya 27, Taman Gaya, 81800 Ulu Tiram, Johor. Our firm focuses mostly on the tastes of Roti John that Malaysians love. We tailor our services to our customers so that they may enjoy themselves and return to our shop. Our service also offers door -to - door delivery service. For those who live in the Johor Bahru area, our price range is also fairly reasonable. We also hire some highly skilled and experienced workers to join our team. To make our business more exciting, we decided to run various promotions for our clients, allowing them to take advantage of the discounts we provide. Our objective is to make our customers happy with our Roti John dishes and ask them to recommend us to their friends and family. We also use high-quality products in our services, so our customers can put their trust in us to serve them with more Roti John menu.